2014
DOI: 10.1177/1352458514525867
|View full text |Cite
|
Sign up to set email alerts
|

Combined visual and motor evoked potentials predict multiple sclerosis disability after 20 years

Abstract: These results further support a role for combined EP-measures as predictors of long-term disability in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
2
43
0
2
Order By: Relevance
“…In 28 prospectively followed adult patients with MS, combined VEP and motor evoked potentials (MEP, central motor conduction time for abductor digiti minimi and anterior tibial muscles) predicated disability, as measured by the EDSS, after 20 years disease duration, accounting for age and therapy status (p 5 0.01). 38 In fact, VEP and MEP predicted 58% of the variability in EDSS at year 20, whereas the baseline EDSS or MRI features (number of T2 hyperintense or gadolinium-enhancing lesions) did not improve the prediction model. Similar studies have not been performed in pediatric MS.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In 28 prospectively followed adult patients with MS, combined VEP and motor evoked potentials (MEP, central motor conduction time for abductor digiti minimi and anterior tibial muscles) predicated disability, as measured by the EDSS, after 20 years disease duration, accounting for age and therapy status (p 5 0.01). 38 In fact, VEP and MEP predicted 58% of the variability in EDSS at year 20, whereas the baseline EDSS or MRI features (number of T2 hyperintense or gadolinium-enhancing lesions) did not improve the prediction model. Similar studies have not been performed in pediatric MS.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…At baseline, the median age was 38 (IQR: 31-45) and disease duration 7 years (IQR: [2][3][4][5][6][7][8][9][10][11][12][13][14]. The majority of patients were in the relapsingremitting phase (RR = 90 %).…”
Section: Resultsmentioning
confidence: 99%
“…Prospective and retrospective studies have demonstrated the good accuracy of models including multimodal EP alone [5,6] or associated with other factors designed to monitor and predict the functional evolution [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…By assessing the functional integrity of neuronal pathways, evoked potentials have been shown to be especially sensitive for subclinical lesions in MS thereby allowing even the prediction of long-term disability (Schlaeger et al, 2014). Since the association between EPs and the BDNF status has not been investigated so far we implemented EPs at 12 months intervals in our study cohort.…”
Section: Discussionmentioning
confidence: 99%